2015
DOI: 10.1152/ajpregu.00228.2014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced insulin signaling in human skeletal muscle and adipose tissue following gastric bypass surgery

Abstract: . Enhanced insulin signaling in human skeletal muscle and adipose tissue following gastric bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
38
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 62 publications
6
38
0
2
Order By: Relevance
“…As Akt activates ribosomal protein S6 kinase, translation may also be playing a role in increased ribosome abundance postsurgery (25). However, a study by Albers et al (16), showed no increase in Akt activity in normoglycemic individuals at 3 months postsurgery. Additional studies would be necessary to explore the factors that regulate the gene expression of ribosomal proteins.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As Akt activates ribosomal protein S6 kinase, translation may also be playing a role in increased ribosome abundance postsurgery (25). However, a study by Albers et al (16), showed no increase in Akt activity in normoglycemic individuals at 3 months postsurgery. Additional studies would be necessary to explore the factors that regulate the gene expression of ribosomal proteins.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, the BMI post-RYGB surgery was on average 35 kg/m 2 , which still is considered obese. Other studies have shown that improvements in glucose disposal occur 6–12 months postsurgery (16,17). Therefore, the lack of improvement in peripheral insulin sensitivity may be more pronounced when weight loss is more extensive.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to early hepatic effects, in both humans and rodents, it is very clear that improvements in peripheral insulin sensitivity and glucose disposal as assessed by hyperinsulinemic euglycemic clamps do not occur until after significant weight loss. In fact, long‐term weight loss–adjusted results suggest that weight loss–independent metabolic effects are important early after surgery but that the sustained weight loss is more of a factor for the long‐term reductions in basal glucose and insulin and consequent reductions in HOMA‐IR .…”
Section: Bariatric Surgery Glucose Homeostasis and T2dm Resolutionmentioning
confidence: 98%
“…Early after surgery (days to ∼2 weeks) the most robust change in glucose homeostasis in patients with frank diabetes or with impaired glucose tolerance is the reduction in fasting plasma glucose and/or insulin levels and consequently homeostatic model assessment for assessing β‐cell function and insulin resistance (HOMA‐IR), an index of insulin sensitivity calculated using fasting glucose and insulin levels. Some of this rapid improvement could certainly occur through removal of glucotoxicity, which affects insulin secretion and insulin‐mediated glucose disposal (i.e., the impact of chronically high glucose levels itself impairs insulin secretion and glucose disposal) .…”
Section: Bariatric Surgery Glucose Homeostasis and T2dm Resolutionmentioning
confidence: 99%
“…Early after RYGB surgery, an enhanced insulin secretion rate and enhanced circulating GLP-1 levels have been documented (10,11). However, it takes months before peripheral insulin sensitivity is detected (9,12), which parallels enhanced muscle expression of GLUT4, enhanced mitochondrial respiration, and enhanced phosphorylation of Akt and TBC1D4 (13)(14)(15). Transcriptomic profiling performed in skeletal muscle before and 6 months after RYGB has documented a partial normalization of alterations detected in obesity, namely, affecting gene pathways related to lipid metabolism or mitochondria (16).…”
mentioning
confidence: 99%